CLASSICAL ART AS A FORMATIVE MECHANISM OF A PERSONAL AESTHETIC EXPERIENCE - Мокляк, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The peculiarities of classical art in the formation of a personal aesthetic experience are analyzed in the article.